FISHING ZONE IN KARIMUNJAWA NATIONAL PARK - Domu Simbolon; Ririn Irnawati; Budy Wiryawan; Bambang Murdiyanto; Tri Wiji Nurani (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2016)
ABSTRACTKarimunjawa National Park (KNP) consists of 7 zones i.e., core, protection, tourism, residence, rehabilitation, cultivation, and traditional fisheries utilization zone. Fishing activities in the traditional fisheries utilization zone (TFUZ) was not optimal because of limited of fishing zone information. The objective of this study was to determine the fishing zone based on major fish for each fishing gear. This study was conducted in KNP from October to December 2009. The major fish resources were determined through analyses of comparative performance index (CPI). Fish resource potential was analyzed by bio-economic model. The existence of fish resources were used as a basis of arrangement of fishing gear arround the fishing zone, through consideration of fishing gear characteristics, the characteristics of waters, the probabilities of conflict, degradation of fish resources, and regulations. Map of fishing zones were created using geographicl information system. Results showed that potential fishes around the TFUZ were reef fishes such as trevallies, yellow tail, and grouper. The potency of reef fishes was about 149 tons/year and pelagic fish of 19,080 tons/year. Fishing zones around the TFUZ consisted of (1) area of 0-3 miles from coastal line which was allocated as the fishing zone of reef fishes using hand line and fish trap, (2) area of 3-4 miles from coastal line which was allocated as demersal fishing zone using bottom gillnet, (3) area of 0-4 miles from coastal line which was allocated as pelagic fishing zone using surface gillnet, and (4) area that more than 4 miles which was allocated as pelagic fishing zone using dynamic fishing gear (troll line), and boat lift net. Keywords: fishing zone, reef fish, pelagic fish, gillnet, Karimunjawa